2015
DOI: 10.1055/s-0035-1565915
|View full text |Cite
|
Sign up to set email alerts
|

Vertiginous Symptoms and Objective Measures of Postural Balance in Elderly People with Benign Paroxysmal Positional Vertigo Submitted to the Epley Maneuver

Abstract: Introduction Benign Paroxysmal Positional Vertigo (BPPV) is one of the most common and treatable causes of peripheral vestibular vertigo in adults. Its incidence increases with age, eventually leading to disability and a decreased quality of life. Objective The research aims to assess short-term effects of Otolith Repositioning Maneuver (ORM) on dizziness symptoms, quality of life, and postural balance in elderly people with Benign Paroxysmal Positional Vertigo. Methods A quasi-experimental study, which evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 45 publications
4
23
0
4
Order By: Relevance
“…In the BPPV+DM group, 5 participants had mild restriction, 3 had moderate and 1 had severe perception of handicap persist after the CRM. Results of our study are similar to others that have shown improvement in DHI scores after resolution of vertigo in people with BPPV (Kasse et al, 2010), with persistence of residual symptoms (Lee, Kwon, & Ban, 2009; Silva, Ribeiro, Freitas, Ferreira, & Guerra, 2016). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the BPPV+DM group, 5 participants had mild restriction, 3 had moderate and 1 had severe perception of handicap persist after the CRM. Results of our study are similar to others that have shown improvement in DHI scores after resolution of vertigo in people with BPPV (Kasse et al, 2010), with persistence of residual symptoms (Lee, Kwon, & Ban, 2009; Silva, Ribeiro, Freitas, Ferreira, & Guerra, 2016). …”
Section: Discussionsupporting
confidence: 91%
“…Although we could not find studies that have examined the FGA after treatment of BPPV, a recent study showed improvement in the Dynamic Gait Index after treatment of BPPV with the CRM (Silva et al, 2016). Like the DHI, there were no differences in performance of functional mobility tasks between groups either before or after resolution of BPPV.…”
Section: Discussionmentioning
confidence: 87%
“…Also supporting previous ndings[2] [20] [32][33], women outnumbered men in our study, which is consistent with the higher prevalence of pc-BPPV in women[34] [35][36]…”
supporting
confidence: 93%
“…Some medications may affect the normal functioning of the vestibular system and cause dizziness 39 , and those people with metabolic syndrome need to use daily medications. Moreover, the sedentary lifestyle is an important risk factor to the dizziness arising, which leads to inactivity and vestibular reflexes inhibition, fear and\or loss of self-confidence 40 .…”
Section: Discussionmentioning
confidence: 99%